Skateboarding, Power and Change - Willing, Indigo; Pappalardo, Anthony (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book explores how cultural, social and political change happens through a unique analysis of the 'ethical turn' in skateboarding today. Insights shared by key change-makers and industry insiders cover themes including First Nations, Black and People of Color, skater-run creative innovations, anti-colonialism, anti-racism initiatives, and a growing focus on equity and empowering skaters historically discriminated against due to gender and/or sexuality. These dynamic changes are also connected to conceptual and theoretical frameworks from skate research, journalism, and sociology. This is a must-read for anyone interested in subcultures and social change.
Skateboarders are Taking a Stance -- Skateboarding Beyond the Looking Glass of Perceived Progressivism -- Change-Makers in Skateboarding -- Formative Experiences, Values, and Outlooks -- Challenges, Strategies, and Change-Making -- Wish Lists, Roadmaps, and Recipes for Skateboarding in the Future -- Stick With It: Legacies, Inheritances, and New Windows.
Keywords: Sociology, Urban; Sports -- Sociological aspects; Sociology; Leisure; Social justice; Urban Sociology; Sport Sociology; Leisure Studies; Social Justice